Circumflex retroesophageal left aortic arch with right ductus arteriosus: A rare complete vascular ring diagnosed on computed tomography angiography - Niraj Nirmal Pandey; Manish Shaw; Sakshi Sachdeva; Gurpreet Singh Gulati; Shyam S Kothari (Wolters Kluwer Medknow Publications, 2020)
A circumflex retroesophageal left aortic arch with a right-sided ductus is an extremely rare cause of a complete vascular ring, which may result in severe tracheobronchial compression, leading to respiratory compromise, especially in children. We present a case of a 6-month-old female child with stridor and feeding difficulties since birth with interspersed self-resolving episodes of cyanosis and apnea, secondary to the presence of the above-mentioned vascular ring.